(untitled) (Research, Society and Development, 2020)
Environmental Interpretation is a tool that, when it is well used, is capable of sensitizing and awakening in people the reflection and critical reading of the context, collaborating with socio-environmental transformation, and causing positive decision making at the face of environmental problems, besides being a strong allied of Environmental Education. Although incipient in Brazil, Environmental Interpretation is an activity that has been shown to be relevant to the theme of environmental causes. In this sense, it can become even more efficient when approached from a critical, holistic and integrative perspective. Within the scope of formal education, the Extension Department of the Federal Institute of Mato Grosso, Cáceres Campus, has been prominent in the diffusion of Environmental Education. In view of this finding, the present research was carry out with the purpose of analyzing how Environmental Interpretation is approached at the Extension Department of the Federal Institute of Mato Grosso, Cáceres Campus, between 2014 to 2018. It is a documentary research with a qualitative approach, and the technique adopted for the production of data was the document analysis. For data analysis, content analysis was used. At the end, it is concluded that the practice of Environmental Interpretation is approached based on strategies that included ecological, environmental, social, and educational aspects, based on environmental sustainability.